"Students were just sticky notes on JamBoard": A first‐year biology teacher's story of 2020–2021. (23rd August 2022) - Weinburgh, Molly H.
Abstract: For decades, a student's preparation for licensure to teach has been rather standard with increased time in field placements culminating with a semester of student teaching. During the Spring 2020, this changed for preservice students scheduled to "student teach." Due to COVID‐19, schools closed for several weeks and re‐opened online. The current wisdom on student teaching and induction is based on research conducted within an in‐person environment. Little research exists on the experiences of these teachers. Therefore, we used an exploratory, descriptive case study design to understand the 18‐month experience of one biology teacher as he navigated student teaching and his first‐year induction. Twenty‐nine conversations were conducted (recorded, transcribed, and analyzed) between March 2020 and May 2021. In addition to telling John's story, the four themes of (a) other ways became the norm, (b) no wisdom from elders, (c) I built it but they did not come, and (d) what happened to hall, bus, club, or cafeteria duty were found. We anticipate the information from this study will help educators rethink and reconstruct science teacher preparation and induction in ways that will help in a nontraditional environment.